DINAMIKA KELOMPOK TANI TERNAK SAPI LM3 DI DESA PINAPALANGKOW KECAMATAN SULUUN TARERAN - Runtunuwu, Omega; Sondakh, B F.J; Rorimpandey, B; Oroh, F. N.S (ZOOTEC, 2016)
ABSTRACT BEEF CATTLE FARMER GROUP DYNAMICS LM3 DISTRICT IN THE VILLAGE PINAPALANGKOW SULUUN TARERAN. The role of the community isÂ  very large in livestock development, thereby fostering community institutions farmers through farmer groups need to be improved. State farmer group members can affect group dynamics through indicators dynamics. The formation of farmer group dynamics is expected to improve income and the welfare of each member of the farmer group. This study aimed to analyze the dynamics of the relationship with the farmer group operating revenues cattle farmer groups LM3 Model Anugerah in the village of Pinapalangkow in Sub District of Suluun Tareran. The study used a survey method, with sampling method is total sampling. Person correlation analysis results obtainedrcount of 0.67 Â of 0.67 which shows there is a relationship between the dynamics and the income of the group members rcount value shows the relationship between the dynamics and the income of the group is a positive relationship, which means that the higher the income the higher the lead group dynamics. The test results showed a statistically significant effect on the dynamics of income groups at the 95% confidence level . Keywords: Dynamics, Farmer Group,Income, Cattle